Comparative production performance of broiler under opened house and closed house system - Muharlien Muharlien; Edhy Sudjarwo; Dyah Lestari Yulianti; Adelina Ari Hamiyanti; Heni Setyo Prayogi (Faculty of Animal Science, Universitas Brawijaya, 2020)
The purpose of this study is to compare the performance of broiler production in a closed and open house system. The study was conducted on September 13-October 25, 2019, at Sumardi's broiler farm located in Kademangan Village, Pagelaran District, and Malang Regency. The material used is 120 broilers in a closed house and 120 broilers in an open house. CP-707 strain broiler chickens were given complete feed produced by PT. Charoen Pokphand Indonesia. Feed and drinking water are given ad libitum. Research variables are feed consumption, body weight, feed conversion, carcass percentage, and abdominal fat weight. Research data were tabulated and analyzed using unpaired t-test. Based on the results of statistical analysis, there is a difference between the performance of broiler production in a closed house and open house system (P<0.05). Closed house system gives a better effect on the performance of broiler production.